2022
DOI: 10.1002/jclp.23375
|View full text |Cite
|
Sign up to set email alerts
|

Self‐compassion and depression in Chinese undergraduates with left‐behind experience: Mediation by emotion regulation and resilience

Abstract: Objectives The protective role of self‐compassion in emerging adult depression has garnered empirical support. It makes more sense to understand the psychological processes underlying this relationship. Based on the stress appraisal patterns, the present study examined the mediating roles of emotion regulation (ER) and resilience in the link between self‐compassion and depression among college students with left‐behind experience (LBE). Methods A total of 391 LBE college students (Mage = 18.43 years; SD = 0.79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Research has shown that the cultural values of individualism are on the rise, and Chinese people are growing more emotionally expressive in contemporary China. 80 , 81 The high school students in the present study from Guangdong Province in China, the pioneer region and frontline of China’s reform policies, are more susceptible to globalization and Western cultures. This might explain why higher expression suppression was linked to higher depression symptoms in our adolescent sample.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Research has shown that the cultural values of individualism are on the rise, and Chinese people are growing more emotionally expressive in contemporary China. 80 , 81 The high school students in the present study from Guangdong Province in China, the pioneer region and frontline of China’s reform policies, are more susceptible to globalization and Western cultures. This might explain why higher expression suppression was linked to higher depression symptoms in our adolescent sample.…”
Section: Discussionmentioning
confidence: 81%
“… 39 According to our findings, emotion regulation is an experiential consequence influenced by strength-based parenting and an internal motive influencing psychological adaptability. 81 Strength-based parenting is a positive parenting approach that enables positive emotion regulation and decreases the danger of negative emotion regulation, which in turn facilitates distress management. This research contributes to the body of knowledge on the psychological benefits of strength-based parenting by presenting preliminary evidence on the potential role of emotion regulation in the negative relationship between strength-based parenting and depression among adolescents in collectivist contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies frequently highlight the connection between self-compassion and depressive symptoms [ 47 , 48 , 49 ]. Self-compassion alleviates negative emotions through positive regulatory strategies such as self-kindness, mindfulness, and common humanity [ 27 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of emotional regulation, self-compassion can enable individuals to engage in cognitive reappraisal and become aware of and understand their current emotional state, thereby alleviating depression. [ 48 ]. Additionally, earlier studies indicated a stronger correlation between depressive symptoms and the negative aspects of self-compassion, while the link between depressive symptoms and positive dimensions of self-compassion appeared relatively weaker [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the primary emphasis in emerging adulthood is on identity exploration, this life stage is associated with frequent changes and uncertainty in all areas of life (Arnett, 2004), which further leads to them to struggle with stress‐related psychological conditions, including anxiety (Keyes et al, 2012), depression (Garlow et al, 2008), and sleep disturbance (Gaultney, 2010). A large number of studies have found the rates of developing maladjustment, such as depression, anxiety, and stress, among LBE college students are significantly higher than their aged‐matched controls in China (Han et al, 2018; Li et al, 2010; Yu et al, 2022; Zhang & Xu, 2022). Depression, anxiety, and stress are indicators of psychological disorders that may adversely affect individuals, for instance, the impairment of normal functions or even health problems (Hj Ramli et al, 2018; Yu, Zhang, et al, 2020; Yu, Zhou, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%